Study on the Oxygen Consumption Rule of Hydroponic Cotton in Different Periods. (5th July 2022) - Fu, Yanbo; Rao, Xiaojuan; Bian, Qingyong; Feng, Yaozu; Huang, Jian; Wang, Zhiguo
Abstract : In this paper, the decay law of dissolved oxygen in the culture solution of cotton in the seedling stage, bud stage, and blossoming and boll-forming stage was studied via hydroponic cotton experiments, and then, the oxygen consumption and its rule of cotton were explored. The results showed that with the increase of the cultivation time, the dissolved oxygen concentration of the cotton at seedling stage, bud stage, and blossoming and boll-forming stage showed an exponential function decrease. The dissolved oxygen concentration of the culture medium decreased from about 7.5 mg·L -1 to a relatively stable dissolved oxygen concentration, which was 4.92 mg·L -1, 1.64 mg·L -1, and 1.82 mg·L -1, respectively. When CK is about 7.1 mg·L -1, a relative equilibrium point between low oxygen absorption rate of cotton and oxygen supply is reached. The sudden drop points of the instant oxygen consumption rate of cotton seedling stage and bud stage are at about 5.15 mg·L -1 and 5.89 mg·L -1, respectively, while the sudden drop point was not obvious at the blossoming and boll-forming stage. The budding cotton can absorb oxygen when the dissolved oxygen in the culture solution is at a higher level. The blossoming and boll-forming stage cotton is more resistant to hypoxia stress.